p53/Surviving Ratio as a Parameter for Chemotherapy Induction Response in Children with Acute Myeloid Leukemia - Rinaldi Lenggana; Susanto Nugroho; Sri Winarsih (Journal of Tropical Life Science, 2016)
Acute myeloid leukemia (AML) is a malignancy that is often found in children. Many studies into the failure of apoptosis function, or programmed cell death, is one of the most important regulatory mechanisms of cellular hemostasis which is closely linked to the development of cancer, are important. Also, regulation of the apoptotic (p53) and anti-apoptotic (surviving) proteins influence treatment outcome. One role of p53 is to monitor cellular stress necessary to induce apoptosis. Surviving (BIRC5) is a group of proteins in the apoptosis inhibitor which works by inhibiting caspase-3. The role of surviving is considered very important in oncogenesis proliferation and cell growth regulation. Chemotherapy in childhood AML can inhibit cell growth and induce slowing as well as stopping the cell cycle. Thus, the aim of this study was to compare p53 and surviving before and after receiving induction chemotherapy in children with AML and also to determine the p53/surviving ratio. Peripheral blood mononuclear cells were collected from AML children before treatment and three months after starting their induction therapy. p53 and surviving were measured by flowcytometry using monoclonal antibodies. Data were analyzed by t-test for comparison between groups and Spearmanâ€™s test to find out the correlation between variables with a significant value of p < 0.05. A total of 8 children were evaluated. The intensity of p53 expression was not significantly increased after induction phase chemotherapy (p = 0.224), but surviving expression and the ratio of p53/surviving were significantly increased in the treatment group compared with the levels prior to chemotherapy (p = 0.002, p = 0.034), and there was a strong negative correlation between p53 and surviving after chemotherapy (r = âˆ’0.63, p = 0.049).